121k views
4 votes
I need it step by step please​

I need it step by step please​-example-1
User Otar
by
4.6k points

1 Answer

10 votes

Answer:

The equation of the line passes through (3, -2) and parallel to the given line:


  • y = 3x-11

The equation of the line passes through (3, -2) and perpendicular to the given line:


  • y=-(1)/(3)x-1

Explanation:

Given the points on the graph line

(2, -1)

(1, -4)

Finding the slope between (2, -1) and (1, -4)


\mathrm{Slope}=(y_2-y_1)/(x_2-x_1)


\left(x_1,\:y_1\right)=\left(2,\:-1\right),\:\left(x_2,\:y_2\right)=\left(1,\:-4\right)


m=(-4-\left(-1\right))/(1-2)


m=3

Equation of the line passes through (3, -2) and parallel to the given line.

We know that parallel lines have the same slope.

so the equation of the line parallel to the given line = 3

Thus, using the point-slope form of the line equation


y-y_1=m\left(x-x_1\right)

where m is the slope of the line and (x₁, y₁) is the point

substituting the values m = 3 and the point (3, -2)


y - (-2) = 3(x-3)


y+2 = 3x-9


y = 3x-9-2


y = 3x-11

Therefore, the equation of the line passes through (3, -2) and parallel to the given line:


y = 3x-11

The equation of the line passes through (3, -2) and perpendicular to the given line

We know that a line perpendicular to another line contains a slope that is the negative reciprocal of the slope of the other line, such as:

slope = m = 3

perpendicular slope = – 1/m = -1/3 = -1/3

Therefore, substituting the values of perpendicular slope = -1/3 and the point (3, -2) in the point-slope form of the line equation


y-\left(-2\right)=-(1)/(3)\left(x-3\right)


y+2=-(1)/(3)\left(x-3\right)

subtract 2 from both sides


y+2-2=-(1)/(3)\left(x-3\right)-2


y=-(1)/(3)x-1

Therefore, the equation of the line passes through (3, -2) and perpendicular to the given line:


y=-(1)/(3)x-1

Conclusion:

The equation of the line passes through (3, -2) and parallel to the given line:


  • y = 3x-11

The equation of the line passes through (3, -2) and perpendicular to the given line:


  • y=-(1)/(3)x-1

User Katarina
by
4.7k points